(untitled) (MAUSAM, 2009)
Three difference cumulus parameterization schemes namely, Kain-Fritsch, New Kain-Fritsch and the Betts-Miller-Janjic are used to simulated convective rainfall associated with two thunderstorm events over Delhi by Advanced Regional Prediction Model (ARPS). An inter comparison of model simulated precipitation in respect of each convection scheme is made with reference to observed precipitation. The study shows that for the Delhi thunderstorm events, the Kain-Fritsch scheme provides more realistic results. This scheme is able to capture the temporal distribution of rainfall and the timely development of thunderstorm in both the cases. While the other two schemes fail to capture these features. However, the Kain-Fritsch scheme is found to overestimate the rainfall amount.